Inauguration of the Br. Andrew Gonzalez FSC Hall - De La Salle University-Manila (Animo Repository, 2007)
De La Salle University inaugurated the 20-storey tall Br. Andrew Gonzalez Hall in time with Br. Andrew's 67 birthday. Aside from the inauguration of the building, the bust of Br. Andrew, done by National Artist Napoleon Abueva was unveiled